فيلون الإسكندري والأثر الفلسفي اليوناني على فكره الديني - عماره, محمد; عماره, نصيره (جامعة الوادي - University of Eloued, 2022)
إن فيلون لاهوتي يهودي، وأفكاره التي طرحها كانت مزيجاً من أفكر فلسفية يونانية، وأفكار دينية من عمق التوراة، وكانت محاولاته قائمة على تلمّس نقاط الاتفاق بين الفكرين، باستعمال طرق الفلاسفة اليونان في تأويل بعض المصطلاحات التي وردت في التوراة، والتي يظهر من خلالها تجسيم وتشبيه الذات الإلهية بالإنسان، فحاول صرفها عن المعنى الظاهري إلى المعنى الباطني، كما رأى أن الفكر الفلسفي ليس بعيداً عن الفكر الديني، فهما يسعيان للوصول إلى الحقيقة، فاليونان توصلوا إليها عن طريق التأمل المجرّد، أما مفكروا اليهود توصلوا إليها عن طريق الوحي الموسوي. لذا كان المنهج اىستقرائي والتحليلي هو الأصح للوصول إلى حقيقة أفكاره، ومنه فنتيجة البحث أن فيلون إستطاع المزج بين الفكرين ليصل إلى نتيجة أن كلاهما ينشدان الحقيقة. Philo is a Jewish theologian, and the ideas he put forward were a mixture of Greek philosophical thoughts and religious ideas from the depth of the Torah, His attempts were based on sensing the points of agreement between the two ideas, using the methods of the Greek philosophers in interpreting some of the terms mentioned in the Torah, through which the embodiment and analogy of the divine self with man appears, He tried to divert it from the apparent meaning to the inner meaning, He also saw that philosophical thought is not far from religious thought, as they seek to reach the truth, as Greece reached it through abstract meditation, while Jewish thinkers reached it through the Mosaic revelation. Therefore, the inductive and analytical method was the most correct to reach the truth of his ideas, and from it the result of the research that Philon was able to combine the two ideas to reach the conclusion that both of them seek the truth.
Philo Of Alexandria And The Greek Philosophical Impact On His Religious Thought
مقال
Keywords: فيلون ; توراة ; اليونان ; الذات الإلهية ; الوحي; Philo ; Torah ; Greeks ; Divine Self ; revelation